Women in the Steel Industry: Closed in Corners or Provided with Possibilities - Salminen-Karlsson, Minna (Nordic Journal of Working Life Studies, 2020)
The steel industry has been one of the basic industries in both Sweden and Finland. It is in a process of change, where research and development play an increasingly prominent role. In Sweden in particular, there is also an ambition to increase the number of women in the industry. This study is based on interviews and workshops with 12 women working in researcher or managerial positions in the Swedish steel industry. Their experiences show that employing more women in the industry is not enough to make effective use of the female talent pool, nor to increase gender equality. Besides belonging to a gender minority, women often had different backgrounds and career paths from their male colleagues, and their organizations need to be able to recognize the value of untraditional characteristics. The organizational environment determined whether these women became just an improvement in gender statistics or real gains in the quest for competence.